Alternative X-ray attenuation material from iodide-starch-gel-based materials - Suriya, Nutjaree; Jantawong, Kunjira; Wongsaroch, Jinnipa; Sawaengteerakul, Napattra; Udomtanakunchai, Chatchanok (Journal of Associated Medical Sciences, 2024)
Background: Iodine is often used as a contrast media because the k-shell binding energy (K-edge) is 33.2 keV, the average energy of a diagnostic X-ray. Thus, iodine can be utilized as a radiation attenuation material for X-rays. Objective: This study aimed to produce low-energy X-ray attenuation materials used as X-ray shielding. A sodium iodide compound will be synthesized by polymerizing mung bean starch with sodium iodide. Materials and methods: The iodide-starch-gel-based material (ISG) was made by mixing a mung bean starch solution (10 %w/w) with a sodium iodide (NaI) solution (100, 200, 250, and 300 mg-Iodine/gm). The linear attenuation coefficient (µ) was determined using radiation dose acquired from the DR plate system and CdTe detector. The X-rays were done at 50 - 120 kVp to study the attenuation properties. Results: The results showed that the linear attenuation coefficient of t ISG was slightly higher than that of sodium iodide solution at the same concentration. The spectrum still shows an X-ray absorption characteristic at about 30.1-40.5 keV K-edge range. Conclusion: Iodide-starch-gel-based components can attenuate X-ray with a K-edge range from 30-40 kVp. The attenuation coefficient of X-ray radiation varies linearly with energy level. Moreover, the concentration of the NaI solution is directly proportional to the attenuation of X-ray radiation. Thus, based on these properties and the gel-like consistency of the substance, it can be developed into a surface coating material to reduce X-ray radiation exposure.